Perlindungan Hukum bagi Jabatan Notaris dalam Pendaftaran Surat di Bawah Tangan (Waarmerking) yang Tanda Tangan Pihaknya Dipalsukan - Flora Jenita Alistya; Rachmadi Usman (Lembaga Yasin AlSys, 2026)
Although the authority of notaries in the registration of privately made documents (waarmerking) has been regulated in Article 15 paragraph (2) of Law Number 2 of 2014 concerning the Position of Notary (UUJN), studies on the legal implications for the notarial office when a forged signature is found in the registered document remain limited. This study aims to analyze the authority of notaries in the implementation of waarmerking and to examine the legal implications and limits of notarial liability when signature forgery occurs in a privately made document. This study used a normative legal method with statutory and conceptual approaches. The primary legal materials included the Indonesian Civil Code and the UUJN, while the secondary legal materials included relevant legal literature, journals, and scholarly works. The data were analyzed qualitatively. The results showed that the authority of notaries in waarmerking is limited to administrative registration, namely providing certainty of date (date certain) without verifying the authenticity of the signature or the truth of the document’s contents. Therefore, legal responsibility for signature forgery principally rests with the perpetrator of the forgery, whereas a notary cannot be held liable as long as the notary has acted within their authority without any element of intent, negligence, or involvement. These findings contribute to the development of notarial law, particularly regarding the limits of liability and legal protection for notaries. The conclusion of this study emphasizes the importance of preventive and repressive legal protection for notaries in the implementation of waarmerking. The implications of this study include theoretical contributions to the development of literature on notarial liability as well as practical implications for notaries, legislators, and the public in clearly understanding the limits of notarial responsibility in the registration of privately made documents.